Aplicações do monitoramento acústico automático de anuros: inventário de espécies, comparações metodológicas e estudo da detectabilidade das espécies - Melo, Isabella Rodrigues de (2020)
The increasing decline in anuran amphibiam populations and the high sensitivity of the group require adequate population monitoring and, studies of natural history and behavior. Bioacoustics can be used for these purposes, because anurans use vocalization as their main form of communication. Using bioacoustics, two types of methodology can be performed: 1) actives searches, where the researcher detect and identify species visually and by aurally in the field, and 2) passive monitoring, where the researcher identifies species vocalizations in acoustic recordings registered by automatic recorders. Passive acoustic monitoring is increasingly being used and is a great strategy for phenology studies. Thus, using passive acoustic monitoring, this work has three main objectives: 1) to complement the anuran species inventory of the Emas National Park; 2) compare the efficiency of active searches and passive acoustic monitoring; 3) to investigate the effect of daily, seasonal variation, methodology and environmental variables on the detection of anuran vocalization activity. For this, during the 2018-2019 breeding season (September-April), we installed seven automated recorders in humid field environments set to recorded vocalizations for two minutes on every hour of the day. At each of the seven points we installed automated recorders, we performed six active searches throughout the breeding season. From the active searches, we found 12 species while by recording analysis we recorded 21 species of anurans, where six of them had not been registered before in the park. Regarding the comparison between methodologies, we found that both techniques (active searching and passive monitoring) are efficient and complementary, since they often detect different species and thus contribute differently to the total richness. We found that species vocalizations are influenced by day period, reproductive season period, precipitation, humidity, temperature and methodology (active search or passive monitoring), depending on the reproductive season period. Thus, we conclude that passive acoustic monitoring is an efficient technique that can assist us in anuran studies.